#1**+10 **

The inverse f is y = x - 1 And the inverse of g is y = x/2

g(f(5) sanys to put 5 into f and then evaluate this in g = 2(5 +1) = 2(6) = 12

And we want to put this result into the inverse of f = 12 - 1 = 11

And we want to put this result into f inverse, again = 11 - 1 = 10

And we want to put this result into g inverse = 10/2 = 5

Finally, we want to put this result into f = 5 + 1 = 6

CPhill
Nov 14, 2014

#1**+10 **

Best Answer

The inverse f is y = x - 1 And the inverse of g is y = x/2

g(f(5) sanys to put 5 into f and then evaluate this in g = 2(5 +1) = 2(6) = 12

And we want to put this result into the inverse of f = 12 - 1 = 11

And we want to put this result into f inverse, again = 11 - 1 = 10

And we want to put this result into g inverse = 10/2 = 5

Finally, we want to put this result into f = 5 + 1 = 6

CPhill
Nov 14, 2014